EFEKTIVITAS PENYERAPAN ANGGARAN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN ACEH BARAT - Salsabila; Wahyuningsih, Yayuk Eko (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the level of effectiveness of budget absorption at the Education and Culture Office of West Aceh Regency. The scope taken by the author is the education budget for 2017 – 2022. The research analysis used is an analysis of effectiveness. The results showed that the level or criteria for the effectiveness of budget absorption at the Education and Culture Office of West Aceh Regency in 2017-2021 had varying effectiveness criteria. The highest level of effectiveness in 2017 and the lowest occurred in 2021. Furthermore, in 2017 the effectiveness criteria were very effective, in 2018 to 2021 the effectiveness criteria were effective. This shows that the effectiveness of budget absorption that has been budgeted has been well implemented by the Education and Culture Office of West Aceh Regency, for a period of 5 (five) years from quite effective to very effective. To the Education and Culture Office of West Aceh Regency to continue to be able to maintain this achievement